Women's Representation and Capital Punishment. (1st October 2016) - Moreland, Amy; Watson, David
ABSTRACT: Although the effects of women's representation have received significant attention, existing research often emphasizes the impact of women's representation on issues directly related to women. Researchers have devoted less attention to the influence of women legislators on policies that are not clearly related to gender. We argue that this gap in the literature is noteworthy for capital punishment policies, because researchers have frequently identified a gender gap in public attitudes toward the death penalty. Through an analysis of capital punishment laws in 125 countries, this study finds that women's legislative representation is significantly correlated with the abolition of capital punishment.